INOVASI PENINGKATAN PENDAPATAN DESA (KASUS DESA KARANG PUCUNG, TAMBAK, BANYUMAS) - Wijaya, Shadu Satwika; Purnawan, Hendi (Jurnal Inovasi Daerah, 2023)
Village autonomy gives flexibility to villages in managing their finances, including managing village income. For this reason, the management of state finances, including villages, must comply with the principles of efficiency, effectiveness and accountability. Village autonomy gives freedom to villages in planning, managing and allocating village income. However, this freedom also requires great responsibility in carrying out its financial management properly, in accordance with the principles of public finance. In an effort to increase village income, villages can also develop innovations in the field of financial and business management, such as developing village-owned enterprises or empowering village communities to become entrepreneurs. However, village financial management still faces various challenges, such as the lack of human resource competence and ineffective supervision. The aim of the research is to identify innovations in increasing the village's original income through Village Owned Enterprises. The research method used in this article is descriptive qualitative with data collection through Focus Group Discussion (FGD) with stakeholders. The results of the study show that innovation in increasing village income through Village Owned Enterprises can be carried out through proper income collection techniques, increasing human resource competencies, strengthening internal controls, and compliance with regulations. These innovations need to be carried out continuously to improve the welfare of village communities and strengthen village autonomy. The conclusion of the study is that there is an appropriate system innovation to increase the income of Karang Pucung Village.